Acquired resistance to EGFR tyrosine kinase inhibitors is mediated by the reactivation of STC2/JUN/AXL signaling in lung cancer - Liu, Yi‐Nan; Tsai, Meng‐Feng; Wu, Shang‐Gin; Chang, Tzu‐Hua; Tsai, Tzu‐Hsiu; Gow, Chien‐Hung; Chang, Yih‐Leong; Shih, Jin‐Yuan (International journal of cancer, 2019)
Constitutive activation of the epidermal growth factor receptor (EGFR) signaling pathway is implicated in the initiation and progression of lung cancer. EGFR tyrosine kinase inhibitor (TKI)‐targeted therapy has become the standard treatment for nonsmall cell lung cancer (NSCLC) patients. However, acquired resistance to these agents remains a major obstacle for managing NSCLC. Here, we investigated a novel strategy to overcome EGFR TKI resistance by targeting the stanniocalcin 2 (STC2)‐JUN‐AXL pathway. We revealed that STC2 was expressed at significantly higher levels in EGFR TKI‐resistant cells. Further, clinical analysis showed that STC2 expression was increased after the development of EGFR TKI resistance and that higher levels were correlated with shorter progression‐free survival in EGFR TKI‐treated lung cancer patients. Moreover, STC2 overexpression in EGFR TKI‐sensitive cells resulted in EGFR TKI resistance. Conversely, genetic silencing of STC2 rendered EGFR TKI‐resistant cells more sensitive to EGFR TKIs. Mechanically, STC2 enhanced AXL promoter activity by increasing the phosphorylation of c‐Jun, which is an indispensable transcription factor that transactivates AXL. STC2 promoted activation of the JUN‐AXL‐extracellular signal‐regulated kinase (ERK) signaling axis in lung cancer cells. Pharmacological or genetic inhibition of AXL‐ERK activity inhibited STC2‐mediated EGFR TKI resistance. We also demonstrated that PE2988 cells, a C797S‐independent osimertinib‐resistant primary cancer cell line from a lung cancer patient, responded to combined AXL inhibitor and osimertinib treatment. In conclusion, our research indicates that STC2 overexpression is important for acquired resistance to EGFR TKIs and that STC2‐JUN‐AXL‐ERK signaling might be a potential therapeutic target to overcome resistance to EGFR TKIs. What's new? EGFR tyrosine kinase inhibitor (TKI)‐targeted therapy has become the standard treatment for non‐small cell lung cancer (NSCLC), but acquired resistance remains a major obstacle. Although several mechanisms of resistance have been identified, much additional information is needed to understand and overcome resistance to EGFR‐TKIs. Here, the authors show that STC2 expression is upregulated in lung adenocarcinomas following the acquisition of resistance, and that its expression is inversely correlated with progression‐free survival. Moreover, the data show that STC2 modulates the activation of c‐Jun/AXL/ERK signaling to confer resistance, highlighting STC2 as a potential therapeutic target in NSCLC.